Queen of Halloween - Engelbreit, Mary. (New York : HarperCollinsPublishers, 2008)
When Ann Estelle and her friend Michael go trick-or- treating and approach a big scary house, they both learn that courage means also being afraid.
Accelerated Reader AR
Keywords: Halloween -- Juvenile fiction; Fear -- Juvenile fiction; Courage -- Juvenile fiction